Toward a Neurobiologically Plausible Model of Language-Related, Negative Event-Related Potentials - Bornkessel-Schlesewsky, Ina; Schlesewsky, Matthias (Frontiers in Psychology, 2019)
Language-related event-related potential (ERP) components such as the N400 have traditionally been associated with linguistic or cognitive functional interpretations. By contrast, it has been considerably more difficult to relate these components to neurobiologically grounded accounts of language. Here, we propose a theoretical framework based on a predictive coding architecture, within which negative language-related ERP components such as the N400 can be accounted for in a neurobiologically plausible manner. Specifically, we posit that the amplitude of negative language-related ERP components reflects precision-weighted prediction error signals, i.e. prediction errors weighted by the relevance of the information source leading to the error. From this perspective, precision has a direct link to cue validity in a particular language and, thereby, to relevance of individual linguistic features for internal model updating. We view components such as the N400 and LAN as members of a family with similar functional characteristics and suggest that latency and topography differences between these components reflect the locus of prediction errors and model updating within a hierarchically organised cortical predictive coding architecture. This account has the potential to unify findings from the full range of the N400 literature, including word-level, sentence- and discourse-level results as well as cross-linguistic differences.